Clerical households in late Medieval Italy - Cossar, Roisin (I Tatti studies in Italian Renaissance history., 2017)
This book takes up the familiar topic of church reform in the later Middle Ages, but does so in a novel way: by examining the relationship between reform and the domestic lives of parish priests, their female companions, and other members of the priests' households or familia in the fourteenth century. Focusing on northern Italy, including Venice, and drawing on a wide range of archival records, the book challenges traditional characterizations of the late medieval clergy as "corrupt." Instead, it shows priests responding to the regulation of their domestic lives. They responded by carefully shaping written records in which household members appeared, for instance by presenting their sexual partners as servants and their children as apprentices. The book also traces, in many cases for the first time, the life cycle and status of priests' kin and household members, including their female companions, children, mothers, and slaves. In addition, the book explores both the work and material cultures of the clerical household in the decades after the Black Death. Throughout, the author argues that the priest's household was a community with roots in both ecclesiastical and lay society. Approaching the history of church reform through the lens of the clerical household, the book provides a new perspective on the history of the Christian church and domestic life in Italy at the beginning of the Renaissance.--